Temporary address and other stories - Beherā, Rāmacandra (Authorspress, 2010)
Gopapura -- The newcomer -- Temporary address -- Lust for life -- Thirst -- The post office -- Two brackets -- Following an interview -- A mean world -- Second cremation -- The last scene